1975
DOI: 10.2307/3428408
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metals: A Toxicological Appraisal of Potential New Environmental Contaminants

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The National Institute of Environmental Health Sciences (NIEHS) andBrogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, such dose levels are many times those that would ever be expected to occur in the general environment. Nevertheless, since exposure to Pt appears to alter certain behavior of the mouse, tOe possibility of subtle adverse biological and behavioral effects resulting from long-term low levei (environmental) exposure of humans cannot be disregarded especially in the light of the fact that Pt can be methylated (26) in a manner analagous to that of mercury (27). By altering its physicochemical properties, methylation may, as in the case of mercury (28) greatly enhance the toxicity of Pt and its bioaccumulatability.…”
Section: Resultsmentioning
confidence: 99%
“…However, such dose levels are many times those that would ever be expected to occur in the general environment. Nevertheless, since exposure to Pt appears to alter certain behavior of the mouse, tOe possibility of subtle adverse biological and behavioral effects resulting from long-term low levei (environmental) exposure of humans cannot be disregarded especially in the light of the fact that Pt can be methylated (26) in a manner analagous to that of mercury (27). By altering its physicochemical properties, methylation may, as in the case of mercury (28) greatly enhance the toxicity of Pt and its bioaccumulatability.…”
Section: Resultsmentioning
confidence: 99%
“…Brubaker et al (28) raised the issues of release and fate of platinum in the environment. In the GM study (11), a limited number of determinations of emission rate for platinum were reported.…”
Section: Release Rate Of Catalyst Components To the Environmentmentioning
confidence: 99%
“…cisPt has been found to inhibit various enzymes [1][2][3], by a mechanism which in some cases includes the interaction with sulfhydryl groups in the enzyme [3], In addition to its therapeutic use. platinum is also an environmental contaminant [4], Various salts of platinum that are environmentally important have been shown to inhibit hepatic microsomal drug metabolism after acute administration [2], Since platinum con tent has been shown to be high in micro somal fractions of both liver and kidney after ip administration of cisPt [5], it might be expected that this drug would have the same effect on hepatic drug metabolism as has been shown for environmental platinum. Preliminary data suggest, however, that ef fects on hepatic drug metabolism observed one day after single or multiple injections of cisPt are minimal [6], Even though platinum is distributed to both liver and kidney, hepa-totoxicity is rarely reported [7,8], The most serious toxic effect of cisPt administration is on the kidneys.…”
Section: Introductionmentioning
confidence: 99%